Application of Nonlinear Finite Element Analysis on Shear-Critical Reinforced Concrete Beams - Asdam Tambusay; Priyo Suprobo; Benny Suryanto; Warren Don (Institute for Research and Community Services, Institut Teknologi Bandung, 2021)
This paper presents the application of a smeared fixed crack approach for nonlinear finite element analysis of shear-critical reinforced concrete beams. The experimental data was adopted from tests undertaken on twelve reinforced concrete beams by Bresler and Scordelis in 1963, and from duplicate tests undertaken by Vecchio and Shim in 2004. To this end, all beams were modeled in 3D using the software package ATENA-GiD. In the modeling, the nonlinear behaviors of the concrete were represented by fracture-plastic constitutive models, which were formulated within the smeared crack and crack/crush band approaches. The applicability of nonlinear analysis was demonstrated through accurate simulations of the full load-deflection responses, underlying mechanisms, crack patterns, and failure modes of all 24 beams. Detailed documentation of the results is presented to demonstrate the potential and practical value of nonlinear finite element analysis in providing an informed assessment of the safety and performance of reinforced concrete structures.